Method for separating and recovering base material

By immersing the laminate in the detachment liquid and using a combination of an alkaline compound, a surfactant with an HLB value of 7 or more, and a defoaming agent, the problems of reduced detachability and re-adhesion in the prior art are solved, and an efficient base layer is achieved. Material separation, recycling and reuse.

CN119343219APending Publication Date: 2025-01-21아티엔스가부시키가이샤 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380045382.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2023-07-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

When the prior art improves productivity, the detachability decreases, the detached components are finely dispersed and re-adhesed on the plastic substrate, and the reused forming material may cause a reduction in appearance or a decrease in physical properties caused by foreign matters.

Method used

A substrate separation and recovery method is adopted in which the laminate in which the adhesive sheet and the substrate are bonded is immersed in a release liquid containing an alkaline compound, a surfactant with an HLB value of 7 or more, and a defoaming agent to remove the adhesive. To prevent sheet detachment, use a combination of surfactants and defoaming agents with an HLB value of 7 or more to suppress the generation of bubbles and improve the detachability.

Benefits of technology

The efficient departure of sticky slices is achieved, the re -attachment of the disconnection is suppressed, and the pollutant -free substrate is obtained, which is suitable for plastic reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173797610000151
    Figure BDA0005173797610000151
  • Figure BDA0005173797610000161
    Figure BDA0005173797610000161
  • Figure BDA0005173797610000171
    Figure BDA0005173797610000171
Patent Text Reader

Abstract

Provided is a method for separating and recovering a base material, which is suitable for plastic reuse, has excellent release properties of an adhesive sheet even in a laminate obtained by bonding the adhesive sheet, which has an adhesive layer and a support body having a coating amount of 10-100 g / m2, to a base material, and in which re-adhesion of the released components is suppressed. The problem can be solved by a method for separating and recovering a base material, the method being characterized by comprising a step in which the laminate is immersed in a release liquid containing a basic compound, a surfactant having an HLB value of 7 or more, and an antifoaming agent, and the adhesive sheet is released.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for separating and recovering a substrate. Background Art

[0002] In recent years, the amount of general waste or industrial waste generated from plastic films, including packaging, plastic bottles, and other plastic products, has been increasing, and waste disposal has become an important environmental issue.

[0003] As the plastic products, food packaging and packaging bodies using plastic films can be cited, and in such food packaging and packaging bodies, a sheet including an adhesive layer is sometimes attached to form a laminate. Such multi-layered food packaging and packaging bodies have a problem that the materials cannot be recycled because they are mixed with many different types of materials.

[0004] Regarding the material recycling of this type of multilayer packaging material, for example, the following technology is disclosed in Patent Document 1: a laminate including an adhesive layer, i.e., an adhesive layer containing a polyurethane resin having a specified acid value, is treated with an alkaline aqueous solution to remove the adhesive layer, thereby separating and recovering the substrate.

[0005] Patent Document 2 discloses a technique for removing ink from a film using a cleaning solution having an alkaline pH and containing a cationic or anionic surfactant.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-090627

[0009] Patent Document 2: International Publication No. 2013 / 144400 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, in the release process described in Patent Document 1, if the amount of packaging material treated with the alkaline aqueous solution is increased in order to improve productivity, the release property is reduced, and the released components are finely dispersed and reattached to the plastic substrate. In addition, the molding material obtained by recycling such a substrate may cause a reduction in appearance or physical properties due to foreign matter.

[0012] In addition, if the surfactant described in Patent Document 2 is contained in the detachment liquid, bubbles are generated in the detachment process. Moreover, the generated bubbles wrap the components (especially the components with high lipophilicity) dissolved from the adhesive layer to form micelles, and float to the liquid surface of the detachment liquid. On the other hand, when a substrate with a small specific gravity is used, it also floats to the liquid surface of the detachment liquid, so there is a problem that the detached components and the substrate are densely packed on the liquid surface of the detachment liquid, and then the re-attachment of the substrate is deteriorated.

[0013] Furthermore, in packaging materials such as food trays, strong adhesion to the substrate is required to prevent price labels from being removed manually. Therefore, the coating amount of the adhesive layer is generally 10 g / m 2 ~100g / m 2 However, when a packaging material having a relatively thick adhesive layer is reused, the above-mentioned problems tend to become more prominent.

[0014] Therefore, the object of the present disclosure is to provide a method for separating and recovering a substrate, which is suitable for plastic recycling and can be used even when a substrate having a coating amount of 10 g / m 2 ~100g / m 2 In a laminated body in which an adhesive sheet having an adhesive layer is bonded to a substrate, the adhesive sheet is also excellent in releasability, and further, re-adhesion of the detached component is suppressed.

[0015] Technical means of solving problems

[0016] The present inventors have conducted extensive studies and have found that the problems of the present disclosure can be solved in the following aspects, thereby completing the present disclosure.

[0017] [1]: A method for separating and recovering a substrate, comprising separating and recovering a substrate from a laminated body in which an adhesive sheet and a substrate are bonded together, wherein the adhesive sheet has a coating amount of 10 g / m 2 ~100g / m 2 The adhesive layer and the support, the separation and recovery method of the substrate is characterized in that,

[0018] The method comprises the steps of immersing the laminate in a release liquid to release the adhesive sheet.

[0019] The separation liquid contains an alkaline compound, a surfactant having a hydrophilic lipophilic balance (HLB) value of 7 or more, and a defoaming agent.

[0020] [2]: The method for separating and recovering a substrate according to [1], wherein the defoaming agent is at least one selected from the group consisting of emulsion-type silicone compounds, self-emulsifying silicone compounds and non-silicone compounds.

[0021] [3]: The method for separating and recovering a substrate according to [1] or [2], wherein the surfactant comprises at least one of a nonionic surfactant and an anionic surfactant.

[0022] [4]: The method for separating and recovering a substrate according to any one of [1] to [3], wherein the adhesive layer is an adhesive layer comprising an acrylic copolymer, the acrylic copolymer is a copolymer of a monomer mixture containing a (meth)acrylate having a carboxyl group, and the acid value of the acrylic copolymer is 0.1 mgKOH / g to 150 mgKOH / g.

[0023] [5]: The method for separating and recovering a substrate according to any one of [1] to [4], wherein the adhesive layer has a gel fraction of 50% to 100% when immersed in an aqueous sodium hydroxide solution.

[0024] Effects of the Invention

[0025] According to the present disclosure, a method for separating and recovering a base material can be provided, which is suitable for plastic recycling and has excellent releasability of an adhesive sheet and suppresses reattachment of detached components. DETAILED DESCRIPTION

[0026] The present disclosure is described in detail below. In addition, other embodiments are of course also included in the scope of the present disclosure as long as they conform to the purpose of the present disclosure. In addition, in this specification, the numerical range specified by "to" includes the range of the numerical values ​​recorded before and after "to" as the lower limit and upper limit.

[0027] Before describing the present disclosure in detail, the following terms are defined. (Meth)acrylic acid includes acrylic acid and methacrylic acid. (Meth)acrylic acid ester includes acrylic acid ester and methacrylic acid ester. A monomer is a monomer having an ethylenically unsaturated double bond.

[0028] Unless otherwise specified, various components mentioned in the present specification may be used alone or in combination of two or more.

[0029] The present invention discloses a method for separating and recovering a substrate, which comprises the step of immersing a laminated body having an adhesive sheet and a substrate bonded thereto in a release liquid to release the adhesive sheet. 2 ~100g / m 2 The adhesive layer and the support body, in the separation and recovery method of the substrate, the separation liquid contains an alkaline compound, a surfactant with an HLB value of 7 or more, and a defoaming agent.

[0030] The detaching liquid contains an alkaline compound and a surfactant with an HLB value of 7 or more, which can promote the detachment of the adhesive sheet and inhibit the detached components (such as adhesive components from the adhesive layer) from reattaching to the detached substrate, so that the non-polluting substrate can be recovered.

[0031] Defoamers can suppress bubbles generated by surfactants in the defoaming process, but generally have extremely high lipophilicity and a low HLB value of about 1 to 3. Therefore, unlike surfactants with an HLB value of 7 or more, they tend to reduce defoaming properties.

[0032] However, the present application uses a surfactant having an HLB value of 7 or more and a defoaming agent in combination, and can achieve both excellent releasability and reattachment even when the amount of the laminate relative to the release liquid is increased. The reason for this is presumably that the generation of bubbles is suppressed, and further, the defoaming agent in the release liquid is in a stable state due to affinity with the component released from the adhesive layer, so that the improvement in releasability brought about by the surfactant is not impaired, thereby exerting excellent reattachment.

[0033] <Separation and recovery method>

[0034] The method for separating and recovering a substrate disclosed in the present invention comprises the step of immersing a laminated body having an adhesive sheet and a substrate bonded thereto in a releasing liquid to release the adhesive sheet, wherein the adhesive sheet has a coating amount of 10 g / m 2 ~100g / m 2 The adhesive layer and the support body, the release liquid contains an alkaline compound, a surfactant with an HLB value of 7 or more, and a defoaming agent.

[0035] In the present disclosure, "detachment" means that the adhesive layer is peeled off by dissolving or swelling by the release liquid, thereby the adhesive sheet is detached from the laminate, including two methods: the adhesive layer is detached by dissolving and the adhesive layer is detached by neutralization, swelling, etc. even if it does not dissolve.

[0036] The purpose of the present disclosure is to obtain a substrate after the adhesive sheet is detached as a reuse substrate or a regenerated substrate, so it is preferred to remove as much adhesive sheet as possible from the substrate. Specifically, the removal rate of the adhesive sheet having an adhesive layer and a support on the surface of the substrate is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more relative to the area of ​​the adhesive sheet before detachment. The substrate recovery process after immersing the adhesive sheet in a detaching liquid to detach it can freely select specific gravity difference separation or size separation according to the material of the support material or the substrate.

[0037] <Separation fluid>

[0038] The stripping liquid may be any substance that contains an alkaline compound, a surfactant having an HLB value of 7 or more, and a defoaming agent, and that causes the adhesive layer to swell and dissolve, and is preferably an aqueous solution from the perspective of maintaining the properties of the recycled material using the recovered polyolefin substrate. These stripping liquids may also be heated.

[0039] [Basic compounds]

[0040] As described above, the desorption liquid used in the present disclosure needs to contain a basic compound.

[0041] The alkaline compound is not particularly limited, and for example, sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia, barium hydroxide (Ba(OH)2), and sodium carbonate (Na2CO3) can be preferably used. More preferably, at least one of sodium hydroxide and potassium hydroxide can be used.

[0042] The content of the alkaline compound in the detaching liquid is preferably in the range of 0.5% to 20% by mass, more preferably in the range of 1% to 15% by mass, and further preferably in the range of 2% to 15% by mass, based on the mass of the detaching liquid. If it is within the above range, the detaching liquid can maintain sufficient alkalinity for detaching the adhesive sheet and recovering the substrate by dissolving or swelling the adhesive layer described later.

[0043] [Surfactants with an HLB value of 7 or more]

[0044] Surfactants with an HLB value of 7 or more are mainly responsible for improving the detachability of the adhesive sheet. It is believed that the reason is that the surface tension of the detaching liquid is reduced by the action of the surfactant with an HLB value of 7 or more, and it is easy to penetrate into the adhesive layer, thereby promoting the detachability. In addition, it is believed that the surfactant with an HLB value of 7 or more is adsorbed on the surface of the detached detaching component or the substrate, thereby preventing the adhesive component from reattaching.

[0045] In addition, if the amount of the laminate is increased relative to the separation liquid during separation and recovery, the laminate and the separated substrate tend to curl in the state of being wrapped in the separated adhesive sheet, and it is difficult to completely remove the adhesive layer and the like even if immersed in the separation liquid. However, according to the method disclosed herein, the separation liquid contains a surfactant having an HLB value of 7 or more, and the surfactant is adsorbed on the surface of the laminate and the separated substrate, and curling is suppressed. As a result, the detachability is improved and reattachment can be suppressed.

[0046] The so-called HLB value is an index value related to the affinity of a surfactant for water and oil, and is a value obtained by dividing the HLB value of a substance without a hydrophilic group into 0 and the HLB value of a substance having only a hydrophilic group into 20. The concept of HLB was proposed by William Griffin of Atlas Powder Company in 1949, and several methods for determining it by calculation were proposed, but in the nonionic surfactant of the present disclosure, the HLB value can be obtained by the Griffin method according to the following formula.

[0047] Mode)

[0048] HLB = 20 × [(molecular weight of the hydrophilic group contained in the surfactant) / (molecular weight of the surfactant)]

[0049] The anionic surfactant, the cationic surfactant, the amphoteric surfactant and the like can be determined by the method described later.

[0050] Examples of the hydrophilic group contained in the surfactant include a hydroxyl group and a vinyloxy group.

[0051] It is important that the HLB value of the surfactant in the present disclosure is 7 or more. When the HLB value is 7 or more, as described above, excellent detachability and reattachment properties are exerted. The HLB value of the surfactant is preferably 8 or more, more preferably 10 or more, and most preferably 12 or more. In addition, the HLB value of the surfactant is preferably 20 or less, more preferably 19 or less, and further preferably 17 or less. If the HLB value is 20 or less, the defoaming property is excellent, so it is preferred.

[0052] As the type of surfactant having an HLB value of 7 or more, for example, nonionic, anionic, cationic, and amphoteric surfactants can be listed, and a preferred type and blending amount can be appropriately selected for use according to the required properties. From the viewpoint of release or foaming properties, it is preferred to contain at least any one of a nonionic surfactant and an anionic surfactant.

[0053] Furthermore, it is preferred that the surfactant has a structure in which alkylene oxide (hereinafter also referred to as AO) is added, because the releasability and reattachment properties become good.

[0054] (Nonionic surfactant)

[0055] As a nonionic surfactant, there is no particular limitation as long as the HLB value is 7 or more, but an alkylene oxide adduct to which an alkylene oxide is added is preferred. More preferred are compounds obtained by adding alkylene oxide to alcohols having active hydrogen (alcohol-based nonionic surfactants), compounds obtained by adding alkylene oxide to amines (amine-based nonionic surfactants), or compounds obtained by adding alkylene oxide to fatty acids (fatty acid-based nonionic surfactants). The addition may be either random addition or block addition. In addition, the carbon number of the alkylene oxide is preferably 2 to 4.

[0056] As the nonionic surfactant, an alcohol-based nonionic surfactant obtained by adding an alkylene oxide having 2 to 4 carbon atoms to an alcohol is more preferable.

[0057] [Alcohol-based nonionic surfactant]

[0058] Examples of alcohol-based nonionic surfactants include alkylene oxide adducts of primary or secondary alcohols having a total carbon number of 8 to 24, and alkylene oxide adducts of alkylphenols having a total carbon number of 8 to 12. The primary or secondary alcohols having a total carbon number of 8 to 24 may be saturated or unsaturated.

[0059] Examples of the primary or secondary alcohol having a total carbon number of 8 to 24 include lauryl alcohol, stearyl alcohol, oleyl alcohol, dodecanol, eicosanol, behenyl alcohol, lignoceryl alcohol, and myristyl alcohol.

[0060] In addition, examples of the alkylene oxide added to the alcohol include ethylene oxide, propylene oxide, and butylene oxide, and ethylene oxide is preferred to be essential. The number of moles of the alkylene oxide added is preferably 1 to 100 moles, more preferably 2 to 50 moles, relative to 1 mole of the alcohol or alkylphenol. If it is within the above range, the debonding property is particularly excellent, so it is preferred.

[0061] [Amine nonionic surfactant]

[0062] As the amine-based nonionic surfactant, there can be mentioned alkylene oxide adducts of saturated or unsaturated primary or secondary amines having a total carbon number of 8 to 36. As amines, there can be mentioned: 2-ethylhexylamine, di-2-ethylhexylamine, laurylamine, dilaurylamine, tetradecylamine, di-tetradecylamine, hexadecylamine, di-hexadecylamine, stearylamine, distearylamine, oleylamine, dioleylamine, etc. In addition, the type and addition molar number of the alkylene oxide are the same as those described in the above-mentioned [alcohol-based nonionic surfactant].

[0063] [Fatty acid nonionic surfactant]

[0064] The fatty acid-based nonionic surfactant has no particular structural limitation, and examples thereof include alkylene oxide adducts of higher fatty acids having a total carbon number of 10 to 24, or fats and oils comprising esters of saturated or unsaturated higher fatty acids having a total carbon number of 10 to 24 and glycerol, and alkylene oxide adducts of a mixture of the above fats and oils and a divalent to devastated polyol. The higher fatty acids having a total carbon number of 10 to 24 may be either saturated or unsaturated.

[0065] As the higher fatty acid having a total carbon number of 10 to 24, for example, saturated higher fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, and behenic acid, and unsaturated higher fatty acids such as palmitoleic acid, oleic acid, elaidic acid, linoleic acid, linolenic acid, erucic acid, and ricinoleic acid can be cited. As divalent to dexavalent polyols, ethylene glycol, propylene glycol, glycerol, polyglycerol, sorbitol, sorbitan, sucrose, and the like can be cited. The type and number of moles of alkylene oxide are the same as those described in the item [Alcohol-based nonionic surfactant].

[0066] (Anionic surfactant)

[0067] As the anionic surfactant having an HLB value of 7 or more, a non-soap type is preferable, and examples thereof include a sulfonic acid type anionic surfactant, a sulfate type anionic surfactant, a carboxylic acid type anionic surfactant, and a phosphate type anionic surfactant.

[0068] [Sulfonic acid anionic surfactant]

[0069] Examples of the sulfonic acid-based anionic surfactant include alkylsulfonic acid, alkylbenzenesulfonic acid, alkylnaphthalenesulfonic acid, alkyldiphenylether disulfonic acid, alkylmethyltaurine, sulfosuccinic acid diesters, alkylene oxide adducts of sulfonic acid, and salts thereof. Specific examples include hexanesulfonic acid, octanesulfonic acid, decanesulfonic acid, dodecanesulfonic acid, toluenesulfonic acid, cumenesulfonic acid, octylbenzenesulfonic acid, dodecylbenzenesulfonic acid, dinitrobenzenesulfonic acid, and lauryldodecylphenylether disulfonic acid.

[0070] [Sulfate ester anionic surfactant]

[0071] Examples of the sulfate-based anionic surfactant include sulfate (alkyl ether sulfate), alkylene oxide adducts of sulfate, and salts thereof. Specific examples thereof include lauryl sulfate, myristyl sulfate, and polyoxyethylene lauryl ether sulfate.

[0072] [Carboxylic acid anionic surfactant]

[0073] Examples of the carboxylic acid-based anionic surfactant include alkyl carboxylic acids, alkylbenzene carboxylic acids, alkylene oxide adducts of carboxylic acids, and salts thereof. Specific examples include lauric acid, myristic acid, palmitic acid, stearic acid, polyoxyethylene lauryl ether acetic acid, and polyoxyethylene tridecyl ether acetic acid.

[0074] [Phosphate ester anionic surfactant]

[0075] Examples of the phosphate-based anionic surfactant include phosphates (alkyl ether phosphates), alkylene oxide adducts of phosphates, and salts thereof. Specific examples include octyl phosphate, lauryl phosphate, tridecyl phosphate, myristyl phosphate, hexadecyl phosphate, stearyl phosphate, polyoxyethylene octyl ether phosphate, polyoxyethylene lauryl ether phosphate, and the like.

[0076] The anionic surfactant having an HLB value of 7 or more preferably has an alkyl group having 2 to 24 carbon atoms or an alkenyl group having 2 to 24 carbon atoms, and more preferably has an alkyl group having 8 to 18 carbon atoms. The alkyl group or the alkenyl group may be linear or branched.

[0077] In addition, when the anionic surfactant having an HLB value of 7 or more is an alkylene oxide adduct, examples of the alkylene oxide include ethylene oxide, propylene oxide, and butylene oxide, preferably ethylene oxide. The number of moles of the alkylene oxide added is preferably 1 to 12 moles, more preferably 1 to 8 moles, relative to 1 mole of the alcohol or alkylphenol. When it is within the above range, the releasability is particularly excellent, so it is preferred.

[0078] Examples of the salt constituting the anionic surfactant include metal salts of sodium, potassium, magnesium, calcium, etc. These salts may be used alone or in combination of two or more.

[0079] Among them, from the viewpoint of the releasability and the reattachment property, the anionic surfactant is preferably a sulfonate type or a phosphate type, and more preferably an alkyl sulfonate, a polyoxyalkylene alkyl ether sulfonate, a polyoxyalkylene alkyl ether phosphate, or the like.

[0080] (Cationic surfactant)

[0081] Examples of the cationic surfactant having an HLB value of 7 or more include alkylamine salts and quaternary ammonium salts. Specifically, stearylamine acetate, trimethyl coconut ammonium chloride, trimethyl tallow ammonium chloride, dimethyl dioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercapto pyridinium, poly (vinyl pyridine)-dodecyl bromide, dodecyl benzyl triethyl ammonium chloride, and the like can be used.

[0082] (amphoteric surfactant)

[0083] Examples of the amphoteric surfactant include lauryl dimethylaminoacetic acid betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethylimidazoline betaine, coconut oil fatty acid amide propyl dimethylaminoacetic acid betaine, polyoctyl polyaminoethyl glycine, and imidazoline derivatives.

[0084] These surfactants with an HLB value of 7 or more can be used alone or in combination of two or more. The content of the surfactant with an HLB value of 7 or more in the detachment liquid is based on the mass of the detachment liquid, preferably in the range of 0.01 mass % to 10 mass %. The more preferred value of the lower limit is 0.05, and the further preferred value is 0.1, and the most preferred value is 0.3. The more preferred value of the upper limit is 5 mass %, and the further preferred value is 3 mass %, and the most preferred value is 1 mass %. If it is 0.01 mass % or more, the detachability and reattachment are excellent, so it is preferred, and if it is 10 mass % or less, it is preferred from the viewpoint of defoaming property.

[0085] The HLB of anionic surfactants, cationic surfactants, and amphoteric surfactants is represented by inorganic organic balance (IOB)×10 in an organic concept diagram.

[0086] The so-called IOB in the organic concept diagram refers to the ratio of the inorganic value (IV) to the organic value (OV) in the organic concept diagram, that is, "inorganic value (IV) / organic value (OV)".

[0087] The organic concept map was proposed by Fujita Mu, and its details are described in Pharmaceutical Bulletin, 1954, vol. 2, 2, pp. 163-173; Chemical Field, 1957, vol. 11, 10, pp. 719-725; Fragrance Journal, 1981, vol. 50, pp. 79-82, etc. That is, the root of all organic compounds is set to methane (CH4), and all other compounds are regarded as derivatives of methane. The carbon number, substituent, phase change part, ring, etc. are set to certain values, and their scores are added to obtain the organic value and inorganic value. Then, these values ​​are plotted on a graph with the organic value as the X-axis and the inorganic value as the Y-axis. The organic concept map is also shown in Organic Concept Map - Fundamentals and Applications - (written by Yoshio Koda, Sankyo Publishing, 1984) and the like.

[0088] [Defoaming agent]

[0089] The defoaming agent can exhibit good defoaming properties without reducing the detachability and reattachment properties by using it in combination with the surfactant having an HLB value of 7 or more, and can suppress foaming caused by the surfactant. Examples of the defoaming agent include silicone compounds and non-silicone compounds.

[0090] (Silicone compounds)

[0091] Examples of the silicone-based compound include an emulsion type, a self-emulsifying type, an oil type, an oil complex type, and a solvent type.

[0092] The emulsion type is a silicone defoaming agent that uses an activator to emulsify a silicone oil complex to form an oil-in-water (O / W) emulsion, and examples thereof include: "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical, "FC2913" and "SILFOAM SE47" manufactured by Asahi Kasei Wacker Silicone, "BYK-015" and "BYK-1640" manufactured by BYK-Chemie Japan, and "TEGO Foamex 1488" manufactured by Evonik Japan.

[0093] Self-emulsifying defoamers are silicone-based defoamers that contain 100% of the active ingredient and become an emulsion by dilution and mixing with water. Examples include "KS-540" and "X-50-1176" manufactured by Shin-Etsu Chemical Co., Ltd. and "SILFOAM SD670" and "SILFOAM SD850" manufactured by Asahi Kasei Wacker Silicone.

[0094] Oil-type defoamers are 100% silicone oils that do not contain solvents or additives, and examples thereof include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical, "AK350" and "AK12500" manufactured by Asahi Kasei Wacker Silicone, and "BYK-1770" manufactured by BYK-Chemie Japan.

[0095] The so-called oil-complex type is a silicone-based defoaming agent in which silica particles are blended in silicone oil, and examples thereof include: "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., "SILFOAM SC370" and "PULPSIL 22274VP" manufactured by Asahi Kasei Wacker Silicone, and "BYK-017" and "BYK-018" manufactured by BYK-Chemie Japan.

[0096] The solvent type is a silicone defoaming agent obtained by dissolving silicone oil in a solvent, and examples thereof include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd. and "BYK-019" and "BYK-025" manufactured by BYK-Chemie Japan.

[0097] (Non-silicone compounds)

[0098] Examples of the non-silicone compounds include fatty acid ester compounds, urea resin compounds, paraffin compounds, polyoxyalkylene glycol compounds, acrylate copolymers, ester polymers, ether polymers, amide polymers, emulsified types of mineral oils, polysiloxane adducts, fluorine compounds, vinyl polymers, acetylene alcohol, acrylic copolymers, special vinyl polymers, ethylene glycol, and higher alcohols (octyl alcohol, cyclohexanol, etc.).

[0099] The defoaming agent may be used alone or in combination of two or more. The content of the defoaming agent in the release liquid is preferably in the range of 0.01% to 5% by mass, and more preferably in the range of 0.03% to 3% by mass, based on the mass of the release liquid. If it is 0.01% by mass or more, the defoaming property is excellent, and if it is 5% by mass or less, the release property and reattachment property are excellent.

[0100] The water content in the desorption liquid is preferably 90% by mass to 99% by mass based on the mass of the desorption liquid. When it is within this range, the desorption property is excellent.

[0101] From the viewpoint of good alkali resistance and less reduction in detachability and reattachment when combined with the surfactant having an HLB value of 7 or more, a preferred defoaming agent is at least one selected from the group consisting of emulsion-type silicone compounds, self-emulsifying silicone compounds and non-silicone compounds.

[0102] The release liquid penetrates from the end portion of the laminate and contacts the adhesive layer, dissolving or swelling it, thereby separating the substrate from the adhesive layer. Therefore, in order to efficiently proceed with the release process, the laminate is preferably cut or crushed, and when immersed in the release liquid, the cross section is exposed to the adhesive layer. In this case, the adhesive sheet can be released in a shorter time.

[0103] The temperature of the detachment liquid when the laminate is immersed is preferably in the range of 25°C to 100°C, more preferably in the range of 30°C to 100°C, and particularly preferably in the range of 30°C to 90°C. The immersion time in the detachment liquid is preferably in the range of 1 minute to 24 hours, more preferably in the range of 1 minute to 12 hours, and particularly preferably in the range of 1 minute to 6 hours. The amount of the detachment liquid used is preferably in the range of 50,000 to 100,000 times the mass of the laminate, and more preferably in the range of 100,000 to 10,000 times. In order to improve the detachment efficiency, it is preferred to stir or circulate the detachment liquid. The rotation speed is preferably 80rpm to 5000rpm, more preferably 80rpm to 4000rpm, and most preferably 100rpm to 2500rpm.

[0104] After the adhesive sheet is separated from the laminate and recovered, the obtained base material is washed with water and dried to obtain a reusable base material.

[0105] <Laminated body>

[0106] The laminate used in the present disclosure is a laminate having a coating amount of 10 g / m 2 ~100g / m 2 The adhesive layer and the adhesive sheet of the support are bonded to the substrate.

[0107] (Base material)

[0108] As the substrate, for example, there can be cited: plastic films, polyethylene nonwoven fabrics, polyester nonwoven fabrics, vinylon nonwoven fabrics, etc., containing polyolefin resins such as polyethylene, polypropylene, ethylene-propylene, polyester resins such as polyethylene terephthalate, vinyl acetate resins, polyimide resins, fluorine resins, polyvinyl chloride resins, and resin materials such as cellophane. The substrate can be a single or multiple laminates. In addition, a printed layer for displaying a product name or imparting decoration and beauty, or an outer coating for protecting the printed layer or imparting gloss and other design properties can also be provided on the substrate. From the perspective of detachability or reusability after separation and recovery, it is preferably free of a printed layer or an outer coating.

[0109] (Adhesive sheet)

[0110] The adhesive sheet has a coating weight of 10 g / m 2 ~100g / m 2The coating amount of the adhesive layer is preferably 12 g / m 2 ~50g / m 2 , more preferably 13g / m 2 ~25g / m 2 In addition, in the present disclosure, the adhesive sheet is a release layer that is released from the laminated body.

[0111] The adhesive sheet can be formed by applying the adhesive composition described below on a support and drying it. Alternatively, it can be formed by applying the adhesive composition described below on a release liner and drying it to form an adhesive layer, and then laminating the support.

[0112] [Support]

[0113] Examples of the support include paper, plastic, rubber, foam, fiber, nonwoven fabric, glass, metal, wood, and the like. Of these, paper and plastic are preferred. As a paper support material, for example, high-quality paper, coated paper, thermal paper, and the like can be used. In addition, there are acidic paper and neutral paper according to the method of fixing the sizing agent (Sizing preparations) on the paper. As a plastic support material, for example, there are polyethylene, polypropylene, polyester, polyimide, and the like. The support may be a single raw material or a laminate. Alternatively, the back side of the support (the side opposite to the side directly bonded with the adhesive layer) may be subjected to a peeling treatment or an antistatic treatment. The thickness of the support is generally 10 μm to 200 μm, preferably 20 μm to 80 μm.

[0114] [Release liner]

[0115] The release liner (sometimes also referred to as a separator) may be any known material without particular limitation. For example, a release liner prepared by treating at least one surface of a suitable substrate (e.g., glassine paper, kraft paper, clay-coated paper, paper laminated with a resin film such as polyethylene, or paper coated with a resin such as polyvinyl alcohol or an acrylic copolymer) with a release agent such as a fluororesin or a silicone resin may be preferably used.

[0116] [Coating method]

[0117] The coating method can use a known technique, by various known coating devices such as a notch wheel coater, a reverse coater, a slot die coater, a lip coater, a gravure chamber coater, a curtain coater, etc., coated on a support or a release liner and dried, thereby obtaining the adhesive sheet of the present disclosure. In addition, at this time, it is preferably dried at 80°C to 120°C after applying an adhesive composition on a release liner, etc. By setting the drying temperature to more than 80°C, an adhesive sheet can be obtained at an appropriate time, and by being set to less than 120°C, thermal degradation of the support or the release liner can be prevented.

[0118] <Adhesive layer>

[0119] The adhesive layer in the present disclosure plays a role in separating the substrate by dissolution and peeling by a release liquid. The resin contained in the adhesive layer includes, for example, acrylic copolymers, urethane copolymers, polyester copolymers, polyamide copolymers, etc., but preferably includes acrylic copolymers.

[0120] In addition, for food packaging applications where no re-peeling occurs, the adhesive layer in the present disclosure preferably has an adhesive force of 3N / 25mm or more in a 180° peel test. The 180° peel test method is as follows. Prepare an adhesive sheet comprising an adhesive layer and a support body having a width of 25mm and a length of 100mm. Under an environment of 23°C and a relative humidity of 50%, peel off a peelable sheet from the adhesive sheet, attach the exposed adhesive layer to a substrate, and perform a reciprocating crimping operation using a 2kg roller. After standing for 24 hours, use a tensile testing machine to peel it off at a speed of 300mm / minute in a 180-degree direction.

[0121] In addition, the gel fraction of the adhesive layer in the present disclosure when immersed in a sodium hydroxide aqueous solution is preferably 50% to 100%, and more preferably 70% to 100%. In the present disclosure, the so-called "detachment" includes two modes: the adhesive layer dissolves and the substrate detaches, and the adhesive layer is detached by neutralization, swelling, etc. even if it does not dissolve. By setting the latter state in which the detachment caused by swelling accounts for the majority, the surface area of ​​the detached adhesive layer can be suppressed to be small, and the effect of preventing re-adhesion brought by the surfactant can be improved.

[0122] The method for determining the gel fraction when immersed in an aqueous sodium hydroxide solution is as follows. The adhesive composition is applied to a polyethylene terephthalate (PET) film so that the dry film thickness becomes about 100 μm, and then dried at 23°C for 7 days. Next, the mass of a 200 mesh metal screen is measured (its mass is set to M). The adhesive sheet produced is cut into a size of 5cm×5cm, and the mass of the test piece attached to the 200 mesh metal screen is measured (its mass is set to A). In addition, 200 mesh is the mesh specified by Japanese Industrial Standards (JIS) G-3555. The test piece is immersed in 50mL of an aqueous sodium hydroxide solution prepared by adding 2 mass parts of sodium hydroxide to 98 mass parts of ion exchange water, and is placed at 60°C for one day. Then take it out, wash it with ion exchange water, dry it at 100°C for 20 minutes, and measure the mass (its mass is set to T).

[0123] Next, the polyethylene terephthalate (PET) film was taken out from the test piece, the adhesive layer was removed using ethyl acetate, and the mass of the PET film was measured (the mass was designated as K). The obtained value was substituted into the following formula (1) to determine the gel fraction.

[0124] Formula (1)

[0125] (TMK)×100 / (AMK)

[0126] (Acrylic copolymer)

[0127] The acrylic copolymer is a copolymer obtained by polymerizing a monomer mixture of (meth)acrylate. Examples of the monomer of (meth)acrylate include (meth)acrylate having a carboxyl group, (meth)acrylate having an alkyl group, (meth)acrylate having an ethylene glycol chain or a propylene glycol chain, and (meth)acrylate having a hydroxyl group. From the viewpoint of the detachability, it is preferred to include a (meth)acrylate having a carboxyl group.

[0128] The acid value of the acrylic copolymer is preferably 0.1 mgKOH / g to 150 mgKOH / g. When the acid value of the acrylic copolymer is 0.1 mgKOH / g to 150 mgKOH / g, it is easier to achieve both adhesive properties and releasability.

[0129] [(Meth)acrylate having a carboxyl group]

[0130] Examples of the (meth)acrylate having a carboxyl group include (meth)acrylic acid, β-carboxyethyl acrylate, ω-carboxypolycaprolactone monoacrylate, 2-acryloyloxyethyl succinate, and 2-acryloyloxyethyl hexahydrophthalate. (Meth)acrylic acid is preferably used in terms of adhesiveness and cost.

[0131] [(Meth)acrylate having an alkyl group]

[0132] Examples of the (meth)acrylate having an alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, and dodecyl (meth)acrylate.

[0133] [(Meth)acrylate having ethylene glycol chain or propylene glycol chain]

[0134] Examples of the (meth)acrylate having an ethylene glycol chain or a propylene glycol chain include methoxy (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, and ethoxypolypropylene glycol (meth)acrylate.

[0135] [(Meth)acrylate having hydroxyl group]

[0136] Examples of the (meth)acrylate having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate, and glycol mono(meth)acrylates such as polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and 1,4-cyclohexanedimethanol mono(meth)acrylate.

[0137] [Other monomers]

[0138] Monomers other than the above may also be used as long as they are monomers copolymerizable with other (meth)acrylates. As other monomers, for example, self-crosslinking monomers such as acetoacetoxyethyl (meth)acrylate, 3-(trimethoxysilyl)propyl (meth)acrylate, 3-(triethoxysilyl)propyl (meth)acrylate, 3-(methyldimethoxysilyl)propyl (meth)acrylate, 3-(methyldiethoxysilyl)propyl (meth)acrylate, vinyl trimethoxysilane, vinyl triethoxysilane, glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl methacrylate, 1,2-epoxy-4-vinylcyclohexane, and amino-containing monomers such as aminomethyl (meth)acrylate, dimethylaminomethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and dimethylaminopropyl (meth)acrylate can be cited. , (meth)acrylamide, diacetone (meth)acrylamide and other amide group-containing monomers, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, N-laurylitaconimide, N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, N-(meth)acryloyl-8-oxyoctamethylenesuccinimide and other imide group-containing monomers, vinyl acetate, styrene, methylstyrene, vinyltoluene, acrylonitrile and other vinyl monomers, etc.

[0139] (Manufacture of acrylic copolymer)

[0140] The acrylic copolymer is a copolymer obtained by polymerizing a monomer mixture of (meth)acrylic acid ester. Examples of the polymerization method include common polymerization methods such as solution polymerization and emulsion polymerization.

[0141] [Manufacturing by emulsion polymerization]

[0142] The acrylic copolymer can be obtained by, for example, emulsion polymerization.

[0143] First, the monomers are mixed to form a uniform mixed solution, which can be directly used for polymerization, or a part or all of water and a surfactant can be added and stirred to form an emulsion and then used for polymerization.

[0144] After preparing these mixed solutions or emulsions, polymerization is carried out in the presence of a polymerization initiator. As a method, the total amount of the mixed solution or emulsion can be loaded into a reaction vessel and polymerization is started, or a part can be loaded into a reaction vessel and polymerization is started and then divided and added several times, or a part can be loaded into a reaction vessel and polymerization is started and the remaining part is continuously dripped, or water and a part or the total amount of surfactant as needed can be loaded into a reaction vessel in advance, and the total amount is continuously dripped. When a mixed solution is used for polymerization, it is preferred to load the total amount of surfactant and a part or the total amount of water into the reaction vessel in advance.

[0145] As a method for adding a polymerization initiator, the total amount can be loaded into a reaction vessel in advance, the total amount can be added after heating, a portion can be loaded into a reaction vessel and then divided and added several times after starting polymerization, a portion can be loaded into a reaction vessel and the remaining portion can be continuously dripped after starting polymerization, or the total amount can be continuously dripped. In the case of split addition or continuous dripping of a polymerization initiator, it can be split and added or continuously dripped in a reaction vessel alone, or it can be split and added or continuously dripped in a state mixed with a mixed solution or an emulsion. In addition, after adding a polymerization initiator by these methods, for the purpose of improving the reaction rate, the polymerization initiator can be added once or twice or more. In this way, the copolymer (A) disclosed in the present invention can be obtained.

[0146] The surfactant used in the emulsion polymerization is preferably appropriately selected from anionic surfactants and nonionic surfactants. In addition, the surfactant may be a reactive surfactant having a free radical polymerizable functional group, or a non-reactive surfactant not having a free radical polymerizable functional group, or both may be used in combination.

[0147] Among surfactants, reactive surfactants are anionic surfactants having one or more radically polymerizable unsaturated double bonds in the molecule, and examples thereof include sulfosuccinate-based surfactants and alkylphenol ether-based surfactants.

[0148] Examples of the non-reactive anionic surfactant include polyoxyethylene polycyclic phenyl ether sulfates, higher fatty acid salts such as sodium stearate, alkyl aryl sulfonates such as sodium dodecylbenzenesulfonate, alkyl sulfate ester salts such as sodium lauryl sulfate, polyoxyethylene alkyl ether sulfate ester salts such as sodium polyoxyethylene lauryl ether sulfate, and polyoxyethylene alkyl aryl ether sulfate ester salts such as sodium polyoxyethylene nonylphenyl ether sulfate.

[0149] Examples of non-reactive nonionic surfactants include polyoxyethylene alkylphenyl ethers such as polyoxyethylene nonylphenyl ether and polyoxyethylene octylphenyl ether; polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; polyoxypolycyclic phenyl ethers such as polyoxyethylene distyrenated phenyl ether; polyoxyethylene sorbitan fatty acid esters, etc. The surfactants may be used alone or in combination of two or more.

[0150] Among the above surfactants, reactive or non-reactive anionic surfactants are preferably used in order to obtain good polymerization stability. The surfactant is preferably used in an amount of 0.5 to 3 parts by mass based on 100 parts by mass of the monomer mixture.

[0151] Emulsion polymerization uses a polymerization initiator. The polymerization initiator may be water-soluble or oil-soluble. However, when an oil-soluble initiator is used, it needs to be dissolved in a water-miscible solvent before use. It is preferred to use a water-soluble polymerization initiator that does not require such a behavior.

[0152] Examples of water-soluble polymerization initiators include potassium persulfate, sodium persulfate, ammonium persulfate, ammonium (amine) salt of 4,4'-azobis-4-cyanovaleric acid, 2,2'-azobis(2-methylamide oxime) dihydrochloride, 2,2'-azobis(2-methylbutyramide oxime) dihydrochloride tetrahydrate, 2,2'-azobis{2-methyl-N-〔1,1-bis(hydroxymethyl)-2-hydroxyethyl〕-propionamide}, and 2,2'-azobis〔2-methyl-N-(2-hydroxyethyl)-propionamide〕. Among these, potassium persulfate and sodium persulfate are preferred.

[0153] The water-soluble polymerization initiator is preferably used in an amount of 0.01 to 1.0 parts by mass, more preferably 0.02 to 0.5 parts by mass, based on 100 parts by mass of the monomer mixture. When used in an amount of 0.01 to 1.0 parts by mass, the polymerization reactivity can be further improved.

[0154] Furthermore, a redox polymerization initiator (using an oxidant and a reducing agent in combination) can be used as the water-soluble polymerization initiator. Examples of the oxidant include ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, benzoyl peroxide, cumene hydroperoxide, and p-methane hydroperoxide. Examples of the reducing agent include sodium sulfite, acidic sodium sulfite, rongalite, and ascorbic acid.

[0155] The redox polymerization initiator is preferably used in an amount of 0.01 to 1.0 parts by mass of the oxidizing agent and the reducing agent, respectively, per 100 parts by mass of the monomer mixture, and more preferably 0.02 to 0.5 parts by mass. 0.01 to 1.0 parts by mass can further improve polymerization reactivity.

[0156] During emulsion polymerization, a buffer may be used to adjust the pH as needed. The buffer is not particularly limited as long as it has a pH buffering effect on the reaction solution of emulsion polymerization. Examples of the buffer include sodium bicarbonate, potassium bicarbonate, monosodium phosphate, monopotassium phosphate, disodium phosphate, trisodium phosphate, sodium acetate, ammonium acetate, sodium formate, ammonium formate, trisodium citrate, and the like.

[0157] The buffer is preferably used in an amount of less than 5 parts by mass, more preferably less than 3 parts by mass, based on 100 parts by mass of the monomer mixture.

[0158] During emulsion polymerization, in order to adjust the molecular weight, a chain transfer agent can be used as needed. Chain transfer agents are generally known to be compounds such as thiol groups or hydroxyl groups. As compounds having thiol groups, for example, mercaptans such as lauryl mercaptan, 2-mercaptoethyl alcohol, dodecyl mercaptan and mercaptosuccinic acid, alkyl mercaptopropionates such as n-butyl mercaptopropionate and octyl mercaptopropionate, alkoxyalkyl mercaptopropionates such as methoxybutyl mercaptopropionate, etc. can be listed. In addition, alcohols such as methyl alcohol, n-propyl alcohol, isopropyl alcohol (isopropyl alcohol (Isopropanol, IPA)), tert-butyl alcohol and benzyl alcohol can also be listed. Chain transfer agents can be used alone or in combination of two or more.

[0159] The amount of the chain transfer agent is preferably 0.01 to 7.5 parts by mass, more preferably 0.03 to 3.0 parts by mass, based on 100 parts by mass of the monomer mixture.

[0160] Furthermore, known additives such as a neutralizer, a leveling agent, an antiseptic, a defoaming agent, a thickener, and a pigment dispersant may be formulated as optional components.

[0161] In order to adjust the pH of the acrylic copolymer, the amount of the neutralizer is preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the acrylic copolymer. By adding 0.1 to 5 parts by mass, the pH of the acrylic copolymer can be adjusted and the storage stability of the acrylic copolymer can be improved.

[0162] The amount of the leveling agent is preferably 0.1 to 1 part by mass relative to 100 parts by mass of the acrylic copolymer. By adding 0.1 parts by mass or more, the leveling property during coating is improved, and depression or shrinkage can be suppressed. By adding 1 part by mass or less, the decrease in adhesion and removability during the formation of the adhesive layer can be suppressed.

[0163] The amount of the preservative is preferably 0.1 to 1 part by mass relative to 100 parts by mass of the acrylic copolymer. By adding 0.1 parts by mass or more, decay or bacterial growth of the water-based adhesive can be suppressed. By adding 1 part by mass or less, the decrease in adhesive strength and removability when forming the adhesive layer can be suppressed.

[0164] The amount of the defoamer is preferably 0.1 to 1 part by mass relative to 100 parts by mass of the acrylic copolymer. By adding 0.1 part by mass or more, foaming during application of the water-based adhesive can be suppressed, and depressions caused by foaming can be suppressed. By adding 1 part by mass or less, the decrease in adhesive strength and removability during the formation of the adhesive layer can be suppressed.

[0165] The amount of the tackifier is preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the acrylic copolymer. By adding 0.1 parts by mass or more, the aqueous adhesive can be thickened, and shrinkage or depression during application can be suppressed. By adding 5 parts by mass or less, the decrease in adhesive force and removability when forming an adhesive layer can be suppressed.

[0166] The pigment dispersion is used when the adhesive layer needs concealment or color development. The amount of the pigment dispersion is preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the acrylic copolymer. By mixing 0.1 parts by mass or more, the concealment or color development of the adhesive layer can be improved. By mixing 5 parts by mass or less, the decrease in adhesion and re-peelability when forming the adhesive layer can be suppressed.

[0167] [Manufacturing by solution polymerization]

[0168] The acrylic copolymer can also be obtained by adding a polymerization initiator to a monomer mixture and performing solution polymerization. The solvent used in the solution polymerization is preferably methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, xylene, hexane, acetone, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, n-propanol, and isopropanol, and more preferably ethyl acetate.

[0169] Solution polymerization is preferably carried out by adding 0.001 to 1 parts by mass of a polymerization initiator relative to 100 parts by mass of the monomer mixture. Typically, polymerization can be carried out under a nitrogen stream at a temperature of about 50° C. to 90° C. for 6 to 20 hours. In addition, a chain transfer agent can be used during polymerization to appropriately adjust the molecular weight of the copolymer.

[0170] Examples of chain transfer agents used in solution polymerization include n-dodecyl mercaptan, mercaptoisobutyl alcohol, thioglycolic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, 2,3-dimercapto-1-propanol, glycidyl mercaptan, α-methylstyrene dimer, carbon tetrachloride, chloroform, and hydroquinone. The chain transfer agent can be used in an amount of about 0.01 to 1 parts by mass relative to 100 parts by mass of the monomer mixture.

[0171] The polymerization initiators used in solution polymerization are generally azo compounds and organic peroxides.

[0172] Examples of azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile) and 2,2'-azobis(2-(2-imidazolin-2-yl)propane).

[0173] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxytrimethylacetate, peroxy(3,5,5-trimethylhexanoyl ester), dipropionyl peroxide, and diacetyl peroxide.

[0174] (Hardener)

[0175] The adhesive layer in the present disclosure may further include a hardener. Examples of the hardener include titanium chelate compounds, aluminum chelate compounds, zirconium chelate compounds, zinc oxide, aziridine compounds, epoxy compounds, isocyanate compounds, carbodiimide compounds, hydrazide compounds, etc. The hardener may be used alone or in combination of two or more.

[0176] The curing agent is preferably blended in an amount of 0.01 to 10 parts by mass, more preferably 0.03 to 8 parts by mass, relative to 100 parts by mass of the acrylic copolymer. By blending 0.01 to 10 parts by mass, adhesion to the substrate and cohesive force are further improved.

[0177] (Adhesion-imparting resin)

[0178] The adhesive layer in the present disclosure may further include an adhesive resin. Examples of the adhesive resin include rosin-based adhesive resins, synthetic hydrocarbon-based adhesive resins, terpene-based adhesive resins, terpene-phenol-based adhesive resins, or emulsions of these resins. By including these adhesive resins, the adhesive force can be further increased.

[0179] Rosin-based adhesion imparting resin is preferably the rosin ester that utilizes alcohol etc. to esterify the unmodified rosin of gum rosin, tall oil rosin, wood rosin or the disproportionated rosin, polymerized rosin, hydrogenated rosin etc. that unmodified rosin is modified, the disproportionated rosin ester, polymerized rosin ester, hydrogenated rosin ester etc. that these modified rosins are further utilized alcohol etc. to esterify to form, the rosin phenol that phenol is added in unmodified rosin etc.. Among these, in order to further improve adhesion and transparency, rosin ester and modified rosin ester are preferably used. In addition, in rosin ester and modified rosin ester, a part of hydroxyl such as the alcohol used in esterification is also unreacted and remains sometimes. The alcohol used in esterification can be listed: the monofunctional alcohols such as methanol, the difunctional alcohols such as ethylene glycol, the trifunctional alcohols such as glycerol and the tetrafunctional alcohols such as pentaerythritol, if consider the compatibility with acrylic copolymer, then preferably the alcohol below trifunctional.

[0180] Examples of the synthetic hydrocarbon-based tackifier resin include coumarone-based resins, coumarone-indene-based resins, styrene-based resins, xylene-based resins, phenol-based resins, and petroleum-based resins.

[0181] The softening point of the tackifier resin is preferably 0°C to 160°C, more preferably 0°C to 120°C, and further preferably 0°C to 100°C. When the softening point of the tackifier resin is 0°C to 160°C, it is easy to achieve both adhesion and release properties. The softening point is a softening temperature measured by the dry bulb method specified in JIS K5902.

[0182] The tackifier resin is preferably used in an amount of 10 to 50 parts by mass, more preferably 15 to 40 parts by mass, based on 100 parts by mass of the copolymer (A). By using 10 to 50 parts by mass of the tackifier resin, it is easy to achieve both adhesive properties and releasability.

[0183] Example

[0184] Hereinafter, the present disclosure will be described in more detail based on Examples, but the present disclosure is not limited to the Examples. In the Examples, "parts" means "parts by mass" and "%" means "% by mass".

[0185] The amounts in the tables are parts by mass, and are converted to non-volatile components excluding water and solvents. A blank column in the table indicates that no compound was added.

[0186] In addition, the acid value of the acrylic copolymer was measured by the following method.

[0187] <Measurement of acid value>

[0188] Accurately weigh 1 g of the acrylic copolymer in a co-stoppered conical flask, add 100 mL of water or a mixed solution of toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) and dissolve it, then titrate it with a 0.1N-alcoholic potassium hydroxide solution. The acid value (unit: mgKOH / g) is calculated by the following formula. In addition, the acid value is set to the value of the dried sample.

[0189] Acid value = {(5.61×a×F) / S} / (non-volatile content concentration / 100)

[0190] S: Sample collection amount (g)

[0191] a: Consumption of 0.1N-alcoholic potassium hydroxide solution (mL)

[0192] F: Factor of 0.1N-alcoholic potassium hydroxide solution

[0193] <Production of acrylic copolymer>

[0194] [Production Example 1-1] (Production of Copolymer (A-1))

[0195] 2.5 parts of tert-dodecyl mercaptan as a chain transfer agent was dissolved in 88 parts of n-butyl acrylate and 12 parts of methacrylic acid. Furthermore, 6.7 parts of Newcol 707SF (aqueous solution of polyoxyethylene polycyclic phenyl ether sulfate salt, 30% active ingredient, manufactured by Nippon Emulsifier Co., Ltd.) as an anionic surfactant and 5.6 parts of a 5% ammonium persulfate aqueous solution as an initiator were dissolved in 35 parts of ion exchange water and stirred to obtain an emulsion. The emulsion was placed in a dropping funnel.

[0196] 72.5 parts of deionized water were placed in a four-necked flask equipped with a stirrer, a cooling tube, a thermometer and the dropping funnel, the air inside the flask was replaced with nitrogen, the internal temperature was raised to 80°C while stirring, and 2.4 parts of a 5% ammonium persulfate aqueous solution were added. After 5 minutes, the emulsion was added dropwise from the dropping funnel over 3 hours.

[0197] The mixture was aged at 80°C for 4 hours with stirring while the internal temperature was maintained at 80°C, and then cooled to obtain a copolymer (A-1).

[0198] [Production Example 1-2 to Production Example 1-8] (Production of Copolymers (A-2 to A-8, A-18))

[0199] Except having changed the kind and compounding amount of monomer, surfactant, and initiator as shown in Table 1, it carried out similarly to [Production Example 1-1], and obtained the copolymer (A-2 to A-8, A-18).

[0200] [Table 1]

[0201] Table 1

[0202]

[0203] [Production Example 1-9] (Production of Copolymer (A-9))

[0204] In a four-necked flask equipped with a stirrer, a cooling tube, a thermometer and the dropping funnel, 94.9 parts of n-butyl acrylate, 0.1 parts of 2-hydroxyethyl acrylate, 5 parts of acrylic acid, 100 parts of ethyl acetate, and 0.015 parts of 2,2'-azobisisobutyronitrile were placed under a nitrogen environment. Stirring and heating were performed to confirm the start of the polymerization reaction, and the reaction was carried out at reflux temperature for 2 hours. Subsequently, 0.005 parts of 2,2'-azobisisobutyronitrile was added to the reaction solution, and the reaction was continued for 6 hours. Then, the reaction vessel was cooled, and 130 parts of ethyl acetate were added to obtain a copolymer (A-9) solution.

[0205] [Manufacturing Example 1-10 to Manufacture Example 1-17] (Manufacture of copolymers (A-10 to A-17))

[0206] Except having changed the kind and compounding amount of a monomer and an initiator as shown in Table 2, it carried out similarly to [Production Example 1-9], and obtained the copolymer (A-10 - A-17).

[0207] [Table 2]

[0208] Table 2

[0209]

[0210] The abbreviations of Table 1 and Table 2 are described below.

[0211] 2EHA: 2-Ethylhexyl acrylate

[0212] BA: n-butyl acrylate

[0213] MA: Methyl acrylate

[0214] MMA: Methyl Methacrylate

[0215] MEA: Methoxyethyl acrylate

[0216] AM-90G: Made by Shin-Nakamura Chemical Industry Co., Ltd., NK ester AM-90G (methoxy polyethylene glycol acrylate)

[0217] HEA: 2-Hydroxyethyl Acrylate

[0218] MAA: Methacrylic acid

[0219] AA: Acrylic acid

[0220] S-710: Made by JNC, Sila-Ace S-710 (3-(trimethoxysilyl)propyl methacrylate)

[0221] 707SF: Made by Nippon Emulsifier Co., Ltd., Newcol 707SF (aqueous solution of polyoxyethylene polycyclic phenyl ether sulfate, active ingredient 30%)

[0222] KH-10: manufactured by Daiichi Industrial Pharmaceutical Co., Ltd., Aquaron KH-10 (polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium salt)

[0223] APS: Ammonium Persulfate

[0224] AIBN: 2,2'-azobisisobutyronitrile

[0225] <Manufacturing of adhesive sheets>

[0226] [Manufacturing Example 2-1] (Manufacturing of Adhesive Sheet (B-1))

[0227] After mixing 30 parts of the copolymer (A-1) and 70 parts of the copolymer (A-2), 0.3 parts of ADEKA NATE B-940 (manufactured by ADEKA Corporation) as a defoaming agent, 0.2 parts of PELEX OT-P (manufactured by Kao Corporation) as a leveling agent, and 0.05 parts of Rebanakkusu FX-360 (manufactured by Shoei Chemical Co., Ltd.) as a preservative were added, and the pH was adjusted (measured using a pH meter D-52 manufactured by Horiba, Ltd.) and the viscosity was adjusted using an alkaline thickener and aqueous ammonia to obtain an adhesive composition having a pH of 8.0 and a viscosity of 2,000 mPa (BL type viscometer #4-12 rpm).

[0228] The obtained adhesive composition was applied in an amount of 15 g / m after drying. 2 The obtained adhesive sheet (B-1) was coated on a releasable sheet using a notch wheel coater, dried in a drying oven at 100° C. for 120 seconds, and then laminated with thermal paper (Ricoh 150LA-1) as a support material.

[0229] [Manufacturing Example 2-2 to Manufacture Example 2-11] (Manufacture of Adhesive Sheets (B-2 to B-11))

[0230] Except having changed the composition and the blending amount as described in Table 3, it carried out similarly to [Production Example 2-1], and obtained the adhesive sheet (B-2 - B-11).

[0231] [Table 3]

[0232] Table 3

[0233]

[0234] [Manufacturing Example 2-12] (Manufacturing of Adhesive Sheet (B-12))

[0235] 0.5 parts of aluminum chelate A (aluminum triacetylacetonate, manufactured by Kawaken Fine Chemicals Co., Ltd.) as a curing agent was added to 100 parts of the copolymer (A-9), and ethyl acetate was added as a solvent to adjust the nonvolatile content to 30% to obtain an adhesive composition.

[0236] The obtained adhesive composition was applied in an amount of 15 g / m after drying. 2 The adhesive sheet 12 (B-12) was obtained by coating the adhesive on a removable sheet using a notch wheel coater, drying in a drying oven at 100°C for 120 seconds, laminating the sheet with thermal paper (150LA-1 manufactured by Ricoh) as a support material, and ripening the sheet at 23°C and 50% relative humidity for one week.

[0237] [Manufacturing Example 2-13 to Manufacture Example 2-27] (Manufacture of Adhesive Sheets (B-13 to B-31))

[0238] Adhesive sheets (B-13 to B-31) were obtained in the same manner as in [Production Example 2-12] except that the composition and blending amount were changed as described in Table 4-1, Table 4-2, and Table 4-3 (hereinafter referred to as Table 4).

[0239] [Table 4-1]

[0240] Table 4-1

[0241]

[0242] [Table 4-2]

[0243] Table 4-2

[0244]

[0245] [Table 4-3]

[0246] Table 4-3

[0247]

[0248] The abbreviations of Tables 3 and 4 are described below.

[0249] SN-385NS: Made by Harima Chemical, Hariester SN-385NS (rosin-based emulsion, base resin softening point 85°C)

[0250] A-75: Super Ester A-75 (rosin ester, softening point 70℃~80℃) manufactured by Arakawa Chemical Industries, Ltd.

[0251] Aluminum chelate A: Aluminum chelate A (aluminum triacetylacetonate) manufactured by Kawaken Fine Chemicals Co., Ltd.

[0252] TETRAD-X: Made by Mitsubishi Gas Chemical Co., Ltd., TETRAD-X (N,N,N',N'-tetraglycidyl-m-xylylenediamine)

[0253] TDI / TMP: trimethylolpropane adduct of toluene diisocyanate (non-volatile content 37.5%)

[0254] The supports shown in Tables 3 and 4 are described below.

[0255] Thermal paper: Ricoh, 150LA-1 (paper thickness 82±9μm)

[0256] Coated paper: manufactured by Oji Paper Co., Ltd., mirror coated gold (cast coat paper containing calcium carbonate, basis weight 84.9 g / m 2 )

[0257] PET: Polyethylene terephthalate film, thickness 50 μm

[0258] PP: Polypropylene film, thickness 40μm

[0259] <Production of separation fluid>

[0260] [Production Example 3-1] (Production of Desorption Liquid (C-1))

[0261] 1 part of polyoxyethylene (POE) alkyl ether A (polyoxyethylene lauryl ether, POE addition number: 4, HLB: 9.7) as a surfactant, 0.1 part of BYK-1650 (manufactured by BYK-Chemie Japan, silicone emulsion defoamer, solid content concentration 27.5%) as a defoamer, 2 parts of sodium hydroxide, and 96.9 parts of water were prepared, and the mixture was stirred using a disperser to obtain a defoaming liquid (C-1).

[0262] [Manufacturing Example 3-2 to Manufacture Example 3-28] (Manufacture of Desorption Liquids (C-2 to C-23, C'-1 to C'-5))

[0263] Except having changed the composition and the blending amount as described in Table 5 and Table 6, it carried out similarly to [Production Example 3-1], and obtained the desorption|elution liquid (C-2 - C-23, C'-1 - C'-5).

[0264]

[0265]

[0266] The abbreviations and materials of Tables 5 and 6 are described below.

[0267] [Surfactant]

[0268] (Nonionic surfactant)

[0269] POE alkyl ether A: polyoxyethylene (POE) lauryl ether, POE addition number: 4, HLB: 9.7

[0270] POE alkyl ether B: POE lauryl ether, POE addition number: 12, HLB: 15.3

[0271] POE alkyl ether C: POE stearyl ether, POE addition number: 12, HLB: 13.9

[0272] POE alkyl ether D: POE oleyl ether, POE addition number: 13, HLB: 13.6

[0273] POE acetylene glycol A: POE addition number: 1.3, HLB: 4.0

[0274] POE acetylene glycol B: POE addition number: 30, HLB: 17

[0275] (Anionic surfactant)

[0276] Sodium lauryl sulfate: HLB: >20

[0277] POE alkyl ether phosphate A: POE alkyl ether phosphate, alkyl carbon number: 12-15, POE addition number: 4, HLB: 13.3

[0278] POE alkyl ether phosphate B: POE lauryl ether phosphate, POE addition number: 4, HLB: 10.0

[0279] (Cationic surfactant)

[0280] Stearyltrimethylammonium chloride: HLB: 8.9

[0281] [Defoaming agent]

[0282] BYK-018: Made by BYK-Chemie Japan, silicone oil composite type, solid content concentration > 97%

[0283] BYK-1770: manufactured by BYK-Chemie Japan, silicone oil type, solid content concentration > 96%

[0284] TEGO Foamex 1448: Made by Evonik Japan, silicone emulsion type, solid content 24%, main solvent: water

[0285] KM-89: Made by Shin-Etsu Chemical Co., Ltd., silicone emulsion type, solid content concentration 34%, main solvent: water

[0286] KS-540: Made by Shin-Etsu Chemical Co., Ltd., silicone self-emulsifying type, solid content concentration 100%

[0287] BYK-015: Made by BYK-Chemie Japan, solid content concentration > 97%

[0288] BYK-1640: manufactured by BYK-Chemie Japan, non-silicone-based, solid content concentration 62%, main solvent: water

[0289] <Manufacturing of laminated body>

[0290] (Production of Laminated Body (D-1))

[0291] The release sheet was peeled off from the adhesive sheet (B-2) under an environment of 23°C and a relative humidity of 50%, and the exposed adhesive layer was attached to a substrate (polyethylene terephthalate film, 200 μm thick) and pressed back and forth once with a 2 kg roller to obtain a laminate (D-1).

[0292] (Manufacture of laminated bodies (D-2 to D-29))

[0293] Laminated bodies (D-2 to D-29) were obtained in the same manner as in laminated body (D-1) except that the adhesive sheet and the substrate were changed to those described in Table 7-1 to Table 7-7 (hereinafter referred to as Table 7).

[0294] The base materials of Tables 7-1 to 7-7 are described below.

[0295] PET: Polyethylene terephthalate film, thickness 200 μm

[0296] PS: polystyrene film, thickness 100 μm

[0297] PP: Polypropylene film, thickness 100μm

[0298] Nonwoven fabric: Asahi-DuPont Flash Spun Products, Tyvek 1073D hard type (polyethylene nonwoven fabric)

[0299] <Separation and recovery of base materials>

[0300] [Example 1]

[0301] In a 1000 mL stainless steel beaker, 400 g of the desorption liquid (C-4) and 12 g of a test piece of 1 cm×1 cm obtained by cutting the laminate (D-1) produced above were placed and stirred at 80° C. and 2000 rpm.

[0302] The PET substrate remaining on the sieve was filtered through a 10-mesh stainless steel mesh, and then washed and dried to separate and recover the substrate.

[0303] [Example 2 to Example 6, Example 8 to Example 23, Example 25 to Example 52, Comparative Example 1 to Comparative Example 5]

[0304] The substrate was separated and recovered by the same steps as in Example 1 except that the laminate and the releasing liquid were changed to those described in Table 7.

[0305] [Example 7]

[0306] In a 1000 mL stainless steel beaker, 400 g of the desorption liquid (C-4) and 12 g of a test piece cut into 1 cm×1 cm from the produced laminate (D-7) were placed and stirred at 80° C. and 2000 rpm.

[0307] The detached base material floating near the surface of the detached liquid is scooped up, washed with water, and dried, thereby separating and recovering the base material.

[0308] [Example 24]

[0309] Separation and recovery were carried out by the same steps as in Example 7 except that the laminate and the desorption liquid were changed to those described in Table 7.

[0310] In the step of immersing the laminate in the releasing liquid to release the adhesive layer in each example, the following evaluation was performed. The results are shown in Table 7.

[0311] <Evaluation Method>

[0312] (Defoaming properties)

[0313] After 10 minutes from the start of stirring, stirring was temporarily stopped and the height of the liquid surface (above the bubbles) was visually observed and evaluated according to the following criteria: The height refers to the volume scale written on the beaker. The larger the value, the higher the liquid surface, that is, the more bubbles were generated.

[0314] A (Excellent): The height of the liquid surface (above the bubbles) during stirring is less than 500 mL

[0315] B (good): The height of the liquid surface (above the bubbles) during stirring is 500 mL or more and less than 700 mL

[0316] C (pass): The height of the liquid surface (above the bubbles) during stirring is 700 mL or more and less than 900 mL

[0317] D (failure): The height of the liquid level (above the bubbles) during stirring is 900 mL or more

[0318] (detachment)

[0319] After 15 minutes, 30 minutes, and 1 hour from the start of stirring, the test pieces were recovered, washed with water, and dried. Each piece was screened by Fourier Transform-Infrared Spectroscopy (FT-IR) and visual screening of the support and substrate, and 10 substrates were sampled. For 3 locations on the front and back of each substrate, a total of 30 locations, FT-IR was used to confirm the presence or absence of absorption peaks of the adhesive layer, and the evaluation was performed according to the following criteria.

[0320] A (excellent): In the substrate collected 15 minutes after the start of stirring, absorption peaks of the pressure-sensitive adhesive layer were observed at less than 5 locations.

[0321] B (good): In the substrate collected 30 minutes after the start of stirring, the number of sites where the absorption peak of the pressure-sensitive adhesive layer was confirmed for the first time was less than 5.

[0322] C (acceptable): In the substrate collected 1 hour after the start of stirring, the number of sites where the absorption peak of the adhesive layer was first confirmed was less than 5.

[0323] CD (practical): In the substrate collected 1 hour after the start of stirring, absorption peaks of the adhesive layer were confirmed at 6 or more locations, but even when the locations were touched with a finger after washing and drying, none of them was sticky.

[0324] D (failure): In the substrate collected 1 hour after the start of stirring, absorption peaks of the adhesive layer were confirmed at 6 or more locations, and at least one location was sticky when the location was touched with a finger after washing and drying.

[0325] (Re-adhesion)

[0326] In the evaluation of detachability, stirring was further performed for 60 minutes from the time point when the absorption peak of the adhesive layer was not confirmed at more than 25 of the 30 locations. Then, the test piece was recovered, washed with water, and dried. Each piece was screened by FT-IR and visually to select the support and substrate, and 10 substrates were sampled. For 3 locations on the front and back of each substrate, a total of 30 locations, FT-IR was used to confirm the presence or absence of the absorption peak of the adhesive layer.

[0327] In the evaluation of the detachability, for the comparative examples with an evaluation result of D, it was determined that the evaluation of the re-adhesion was difficult and was not conducted.

[0328] A (excellent): The number of sites where absorption peaks of the pressure-sensitive adhesive layer were confirmed is less than 5.

[0329] B (good): The number of sites where absorption peaks of the pressure-sensitive adhesive layer were confirmed was 5 or more and less than 8.

[0330] C (pass): The number of sites where absorption peaks of the pressure-sensitive adhesive layer were confirmed was 8 or more and less than 10.

[0331] D (failure): The number of sites where absorption peaks of the adhesive layer were confirmed was 10 or more.

[0332] [Table 7-1]

[0333] Table 7-1

[0334]

[0335] [Table 7-2]

[0336] Table 7-2

[0337]

[0338] [Table 7-3]Table 7-3

[0339]

[0340] [Table 7-4]Table 7-4

[0341]

[0342] [Table 7-5]Table 7-5

[0343]

[0344] [Table 7-6]

[0345] Table 7-6

[0346]

[0347] [Table 7-7]

[0348] Table 7-7

[0349]

[0350] The evaluation results show that the release liquid of the present disclosure can easily release the adhesive sheet from the laminate, and can recover a high-quality substrate with little re-adhesion of the adhesive layer.

[0351] This application claims priority based on Japanese patent application No. 2022-118573 filed on July 26, 2022, and all the contents disclosed therein are incorporated into this application.

Claims

1. A method for separating and recovering a substrate, which is a method for separating and recovering a substrate from a laminated body in which an adhesive sheet and a substrate are bonded, wherein the adhesive sheet has a coating amount of 10 g / m 2 ~100g / m 2 The adhesive layer and the support, the separation and recovery method of the substrate is characterized in that, The method comprises the steps of immersing the laminate in a release liquid to release the adhesive sheet. The separation liquid contains an alkaline compound, a surfactant having a hydrophilic-lipophilic balance value of 7 or more, and a defoaming agent.

2. The method for separating and recovering a substrate according to claim 1, wherein: The defoaming agent is at least one selected from the group consisting of emulsion-type silicone compounds, self-emulsifying silicone compounds and non-silicone compounds.

3. The method for separating and recovering a substrate according to claim 1, wherein: The surfactant includes at least any one of a nonionic surfactant and an anionic surfactant.

4. The method for separating and recovering a substrate according to any one of claims 1 to 3, wherein: The adhesive layer includes an acrylic copolymer, which is a copolymer of a monomer mixture containing a (meth)acrylic acid ester having a carboxyl group, and has an acid value of 0.1 mgKOH / g to 150 mgKOH / g.

5. The method for separating and recovering a substrate according to any one of claims 1 to 3, characterized in that: The adhesive layer has a gel fraction of 50% to 100% when immersed in an aqueous sodium hydroxide solution.

Citation Information

Patent Citations

  • Organic solvent-based printing ink, printed material, and laminate

    JP2020090627A

  • Electromagnetic wave absorbing particles, electromagnetic wave absorbing particle dispersion liquid, electromagnetic wave absorbing particle dispersion, and electromagnetic wave absorbing laminate

    JP2022118573A

  • Method for removing ink printed on plastic films

    WO2013144400A1